Experimental fracture sealing in reservoir sandstones and its relation to rock texture. (December 2021) - Busch, Benjamin; Okamoto, Atsushi; Garbev, Krassimir; Hilgers, Christoph
Abstract: Faults and fractures are important fluid pathways in subsurface energy reservoirs. Especially in geothermal energy production, hydrocarbon production, and energy storage in the subsurface, fractures can enhance reservoir quality and production or storage potential. However, mineral precipitations often reduce available fracture apertures, and thus fracture porosity and permeability. Hydrothermal experimental setups, natural samples, and numerical simulations have been studied to great extent. In fractured sandstones, the main focus has been on only some controlling factors, e.g. fracture opening rate and the orientation of crystallographic axes in substrates. Furthermore, substrates have mostly been fairly homogeneous or sediment textures have not been explicitly considered. Here, fracture sealing experiments are performed on a homogeneous, massive marine sandstone and heterogeneous, laminated fluvial sandstone. Hydrothermal flow-through experiments are performed at 421 ± 1 °C and 30.5 ± 0.5 MPa for 72 h to compare resulting precipitated quartz cement textures on fracture surfaces on natural sandstones. Results indicate a strong impact of grain size variations associated with lamination on observed syntaxial quartz crystal dimensions on fracture surfaces. In layers of finer grain sizes, smaller cement overgrowths develop, as opposed to coarser grained laminae in the same sample. In homogeneous sandstones, the overgrowths appear more uniform, apart from the differences induced by varying c-axis orientations. Some open fracture porosity may be preserved in areas of finer grained laminae, as opposed to coarser grained laminae. Additionally, the potential to stabilize fractures by cement growth spanning the aperture could preserve fracture porosity and permeability in generally unfavorable stress regimes. Furthermore, the relative abundance of suitable syntaxial precipitation sites and additional mineral dissolution as a function of varying detrital compositions appears to influence the mineralogy of the precipitate. If samples are rich in quartz grains, the largest quantity of precipitate will be quartz, due to the large supersaturation in the input solution. If samples contain less quartz by volume, the same solution additionally precipitates phyllosilicates, implying that some structural-diagenetic mineral phases are a function of heterogeneity of the host rock, rather than a result of variable external fluid compositions entering the formation. The phyllosilicates additionally act as nucleation discontinuities, reducing the size of surfaces available for syntaxial precipitation of quartz. Results may be applicable in fractured sandstone lithologies, which have been in the focus of energy storage and production. Highlights: Detrital grain size and rock composition affect fracture cementation. Positive correlation between substrate grain size and overgrowth c-axis length. Additional precipitate forms where host rock is quartz-poor. Sheet silicate formation is sourced from fluid-rock interactions.